Pandemic times (Revista Venezolana de Salud Pública, 2020)
We are living a time of a pandemic of a coronavirus type virus COVID 19, which causes a disease that although 80% of the population runs like any flu with a cold, sore throat, general malaise, cough, fever and it improves quickly, In 20% of the population, this can cause more damage, prolonging and deepening its symptoms, causing respiratory and cardiovascular damage and deterioration of the general condition, meriting hospitalization, specific medical treatment, some will need ventilatory support in an ICU and 2% of these patients will die .